Modelling of fracture problems in quasi-brittle materials by the E-FEM - MARASCA,C. Z. S. (2018)
Abstract In this paper a numerical model with strong discontinuities is presented to address fracture problems in quasi-brittle materials. A non-symmetrical statically and kinematically consistent formulation is implemented. The strong discontinuity in the displacement field is represented using the elemental enrichment finite element method (E-FEM). In other words, the strong discontinuity is introduced into the finite element and the additional degrees of freedom are condensed at the element level, allowing the implementation into existing computational codes. Two constitutive models are used to analyze the behavior of the cracked zone, linear and exponential. The exponential model results are closer to those obtained in experimental data and representative numerical simulations than the linear model.